A New Standardization of the Bells Test: An Italian Multi-Center Normative Study - Mancuso, Mauro; Damora, Alessio; Abbruzzese, Laura; Navarrete, Eduardo; Basagni, Benedetta; Galardi, Giuseppe; Caputo, Marina; Bartalini, Brunella; Bartolo, Michelangelo; Zucchella, Chiara; Carboncini, Maria C.; Dei, Simona; et al. (Frontiers in Psychology, 2019)
Objective: The Bells Test is a cancelation task that is widely used for the diagnosis of unilateral spatial neglect (USN). With the aim of fostering more reliable use of this instrument, we set out to develop new norms adjusted for the possible influence of age, gender and education. We worked on the original version of the test. Methods: Normative data were collected from 401 healthy participants aged between 20 and 80 years. Individual factors that could affect performance (i.e., gender, age, and years of education) were considered. We computed several indices on the Bells Test including an asymmetry score, an accuracy score and execution time. Multiple regression analyses (for time measures) and generalized linear models (for accuracy measures) were used to check for the influence of individual predictors of performance on the Bells Test. Results: Data indicated a significant influence of age on the accuracy score and execution time variables and a marginally significant effect of education on the accuracy score variable. Wherever appropriate, cut-offs are provided for the three dependent scores on the Bells Test corrected for age and education. Conclusion: Based on a large normative sample, the present study provides new normative data on the Bells Test, which could lead to its reliable use in the diagnosis of USN.